2019
DOI: 10.1186/s13020-019-0256-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xinjiaxiangruyin on the TLR7 pathway in influenza virus-infected lungs of mice housed in a hygrothermal environment

Abstract: Background To investigate the effects and immunological mechanisms of the traditional Chinese medicine Xinjiaxiangruyin on controlling influenza virus (FM1 strain) infection in mice housed in a hygrothermal environment. Methods Mice were housed in normal and hygrothermal environments, and intranasally infected with influenza virus (FM1). A high-performance liquid chromatography fingerprint of Xinjiaxiangruyin was used to provide an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Vahl. It effectively reduced lung inflammation and downregulated the mRNA and protein expression levels of TLR7, MyD88, and NF-κB p65 in C57BL/6 mice infected with FM1 in a hot and humid environment (Fu et al, 2019). It was suggested that XJXRY may reduce virus-induced lung injury by downregulating the expression levels of key factors in TLR7 signaling pathway.…”
Section: Xinjiaxiangruyin (Xjxry)mentioning
confidence: 99%
“…Vahl. It effectively reduced lung inflammation and downregulated the mRNA and protein expression levels of TLR7, MyD88, and NF-κB p65 in C57BL/6 mice infected with FM1 in a hot and humid environment (Fu et al, 2019). It was suggested that XJXRY may reduce virus-induced lung injury by downregulating the expression levels of key factors in TLR7 signaling pathway.…”
Section: Xinjiaxiangruyin (Xjxry)mentioning
confidence: 99%
“…Influenza virus is the representative of orthomyxoviridae, including human influenza virus and animal influenza virus [8,9]. Influenza virus infection, whether seasonal or pandemic, often leads to pneumonia, which can cause serious health problems [10,11]. For the treatment of viral pneumonia, apart from neuraminidase inhibitors and ribavirin, other antiviral drugs showed no significant effect on pneumonia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al identified 67 differentially expressed cellular miRNAs between infection with the H5N1 avian influenza virus (HPAI) and the reconstructed 1918 H1N1 influenza virus (r1918) (2:6) [ 14 ]. Influenza A/FM/1/47 (H1N1)(FM1), is commonly used by Chinese researchers to investigate the immune response and inflammatory pathogenesis during IAV infection, and to evaluate the therapeutic and pharmacological effects of Chinese herbs [ 15 21 ]. However, the FM1-induced general changes in the levels of miRNAs and mRNAs remain unclear.…”
Section: Introductionmentioning
confidence: 99%